Clinical efficacy and safety analysis of aumolertinib in real-world treatment of EGFR-mutated advanced non-small-cell lung cancer - Zhang, Xiaojuan; Zhang, Mina; Du, Xinyang; Zhang, Guowei; Niu, Yuanyuan; Wei, Chunhua; Guo, Lanwei; Shi, Chao; Liu, Hangfan; Wang, Huijuan (Frontiers in Pharmacology, 2024)
The study aims to determine the efficacy and safety profile of Aumolertinib in the real word treatment setting for advanced non-small cell lung cancer (NSCLC) patients harboring EGFR mutations.We retrospectively analyzed the clinical data of 173 EGFR-mutated advanced NSCLC patients who received Aumolertinib treatment at Henan Cancer Hospital from April 2020 to December 2022. Progression-free survival (PFS) and overall survival (OS) were evaluated using Kaplan-Meier survival curves, while a Cox regression model was employed for multifactorial analysis and prognostic factor assessment.Results Among patients administered first-line Aumolertinib (n=77), the objective remission rate (ORR) of 77.92% was observed, along with a disease control rate (DCR) of 100%. The median progression-free survival (mPFS) was 24.97 months, which did not reach the median overall survival (mOS). The patients treated with Aumolertinib after progression on prior EGFR-TKI therapy (n=96) exhibited an ORR of 46.88%, a DCR was 89.58%, the mPFS was 15.17 months, and mOS was 21.27 months. First-line treatment multivariate Cox regression analysis demonstrated a statistically significant impact of elevated creatine kinase on PFS(P=0.016), and a similar significant influence of co-mutation on OS (P=0.034). Furthermore, subsequent-line treatment multivariate Cox regression analysis showed a statistically significant impact of elevated creatine kinase on median PFS(P=0.026), and a significant effect on the number of metastatic organs (P=0.017), co-mutation (P=0.035), elevated creatine kinase (P=0.014) on median OS.Aumolertinib proves to be clinically effective and safe in the real world setting for patients with EGFR mutation-positive NSCLC.